DIGITAL SERVICE TRANSFORMATION AT THE SUB-DISTRICT LEVEL: A STUDY OF THE EFFECTIVENESS OF MYBCA SERVICES FOR BCA BANK CUSTOMERS AT THE PONOROGO COKROAMINOTO BRANCH OFFICE - Abdi Pramudya , Rio; Widyawati; Devy Pramudiana, Ika (International Journal of Multidisciplinary Reseach, 2026)
This research aims to describe and analyze the effectiveness of digital service transformation through the myBCA ecosystem at Bank BCA KCP Ponorogo Cokroaminoto within the framework of Public Administration. As the paradigm shifts from Old Public Administration (OPA) toward New Public Service (NPS), public service institutions are increasingly required to prioritize citizen dignity, transparency, and accountability. This study employs a qualitative descriptive approach, using in-depth interviews, passive participatory observation, and documentation to capture the depth of human perception and social interaction in public services. Informants were selected through purposive sampling, including branch management, frontliners (Customer Service and Tellers), and customers. The results indicate that the migration to the myBCA ecosystem has successfully achieved significant service efficiency by shifting routine administrative burdens from bank counters directly to the customers' hands. Through features like Single ID, customers can manage multiple accounts independently, which is particularly beneficial for high-mobility business actors in the Cokroaminoto area. This phenomenon, identified as debureaucratization, allows frontliners to shift their focus from clerical tasks to high-quality consultative services that require empathy and deep analysis. Furthermore, the study finds that the success of digital adaptation is fundamentally supported by the synergy between E-Service Quality and the responsiveness of bank personnel. While the application provides usability and reliability, the role of staff as "digital educators" remains crucial in bridging the digital divide for less tech-savvy customers. Proactive responsiveness and "digital empathy" demonstrated by frontliners and security personnel enhance public trust by ensuring that professional human support is always accessible. In alignment with Law No. 25 of 2009 concerning Public Services, the transparency and real-time information provided by myBCA minimize information asymmetry and strengthen institutional legitimacy. Ultimately, digital efficiency at KCP Ponorogo is defined by a balance between reliable systems and responsive personnel, creating an inclusive and agile banking ecosystem